Port Essington : The Historical Archaeology of a North Australian Nineteenth-Century Military Outpost. - Allen, Jim. (Studies in Australasian Historical Archaeology Series, 2008)
In 1966 Jim Allen undertook the first professional excavation of European site in Australia. The 1840s military settlement of Victoria was established at Port Essington, the northernmost part of the Northern Territory and was the end point of Ludwig Leichhardt's epic journey in 1844-45. This settlement was the longest lived of three failed attempts by the British to establish a settlement on the northern coast of Australia before 1850. Its history reflects many of the dominant themes of wider colonial history - isolation, tropical disease, poorly equipped and inexperienced colonists, inept government bureaucracies and relations with the Indigenous population.